PENGARUH PERSEPSI KUALITAS LAYANAN, TERHADAP PROSES KEPUTUSAN MEMILIH PONDOK PESANTREN DENGAN KEPERCAYAAN DAN CITRA LEMBAGA SEBAGAI VARIABEL INTERVENING - Muhammad Iftor Nawawi; Dikdik Harjadi; Dede Djuniardi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The phenomenon of this research is oriented towards the decision process of choosing a student guardian for the Nurul Huda Kertawangunan Islamic Boarding School. The population in this study were all student guardians representing students at the Nurul Huda Kertawangunan Special Islamic Boarding School for SMPIT, MA and SMAIT levels for the 2022/2023 academic year, totaling 468 student guardians. Respondents who filled out the questionnaire were 228 santri guardians. The research results found that the perception of the quality of educational services had a significant positive effect on trust and image of the institution, but had an insignificant positive effect on the choice decision process. Trust has an insignificant positive effect on the voting decision process. The image of the institution has a significant positive effect on the voting decision process. The influence of perceived quality of educational services on the choice decision process cannot be mediated by trust, but can be mediated by the image of the institution.